(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Water samples collected from some selected ponds of Meherpur region were studied for the presence of organophosphorus and carbamate pesticide residues. High performance liquid chromatography (HPLC) technique was used to determine the concentration levels of those residues. The results obtained indicate slight contamination of some of the water samples with residues of diazinon, chlorpyriphos (organophosphorus insecticide) and carbofuran (carbamate insecticide). The residues level of diazinon and chlorpyriphos ranged from 0.033 to 0.079 ppm and 0.010 to 0.471 ppm respectively. Among carbamate pesticides, carbofuran identified in two samples ranged from 0.0143 to 0.0387 ppm, and carbaryl was not detected in any of the samples. Limit of detection (LOD) was 0.01 ppm. However, the residue level was also within the acceptable ranges according to the WHO guideline value of water quality. But, the presence of such residues is indicative of weak regulatory control which is required to be in place for safety of the environment and to stop further aggravation of the situation. J. Asiat. Soc. Bangladesh, Sci. 39(1): 77-82, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16036